Temporal Trends of Dog Bite Cases and their Correlation with Meteorological Factors in a Metropolitan City - Dinesh Asokan; Anjali Mall; Lalit Sankhe; Nagaraj Jaganathasamy; Geeta Pardeshi (Indian Journal of Community Medicine)
Background: Dog bites are a major public health concern in India. Understanding the temporal trends of dog bites and their correlation with meteorological data will help develop effective strategies for prevention under one health program. Assessment of temporal trends of dog bite cases and their correlation with meteorological factors. Methodology: A retrospective secondary data analysis was conducted using the data of 2022 dog bite cases reported at a tertiary care hospital in Mumbai. The month-wise temporal trend was described, and its correlation was assessed with meteorological data retrieved from the regional meteorological center by using Spearman’s correlation coefficient. Conclusion: Of the 3350 dog bite cases that attended the outpatient department, 2368 (70.7%) were below 40 years of age, 2733 (81.6%) were males, and 2621 (78.18%) had category III bites. We found a positive correlation between the number of dog bites and temperature (ρ = 0.650, P = 0.022) and average sun hours (ρ =0.804, P = 0.002). A negative correlation was found between rainfall (ρ = −0.845, P = 0.001), humidity (ρ = −0.730, P = 0.007), and rainy days (ρ = −0.804, P = 0.002). A similar correlation pattern was found for category III bites.